Atividade antiulcerogênica do carveol e da hesperetina e anti-inflamatória intestinal do carveol em modelos animais - Pessoa, Matheus Marley Bezerra (2023)
The monoterpene carveol and the flavonoid hesperetin are secondary metabolites present in various medicinal plants, such as Mentha spicata (spearmint) and Citrus aurantium (orange), respectively. Pharmacological studies already indicate their anti-inflammatory, antioxidant, and gastroprotective effects. Thus, the present study aimed to evaluate the gastric and duodenal antiulcerogenic activity of hesperetin and carveol, along with their related mechanisms of action. Additionally, the acute intestinal anti-inflammatory activity of carveol was assessed in animal models. Using the acetic acid-induced gastric ulcer model, the repeated dose toxicity of carveol and hesperetin was investigated over 14 days. The results showed that both substances did not alter (p>0.05) organ weights (heart, liver, spleen, and kidneys), biochemical parameters, or hematological parameters. It was also observed that the test substances protected animals from reduced water and food consumption and weight loss. In the evaluation of gastric healing activity, treatment with carveol and hesperetin at their optimal doses (100 mg/kg, p.o.) for 14 days reduced (p<0.05) the ulcerative lesion area (ULA) compared to control groups. These effects were associated with an increase (p<0.05) in GSH, SOD, and IL-10 levels and a decrease (p<0.05) in MDA, MPO, IL-6, IL-1β, and TNF-α levels. Furthermore, oral administration (p.o) of carveol and hesperetin at all evaluated doses (25, 50, 100, and 200 mg/kg) reduced (p<0.05) ULA in the duodenum of rats subjected to cisteamine-induced lesions. This effect may be related to an increase (p<0.05) in GSH and SOD levels and a decrease (p<0.05) in MDA and MPO levels. In the acute TNBS-induced intestinal inflammation model, carveol at all doses (25, 50, 100, and 200 mg/kg, p.o.) promoted a reduction (p<0.05) in the macroscopic injury score, ULA, the weight/length ratio, and diarrheal index. In colon samples from this model, its optimal dose (100 mg/kg) reduced (p<0.05) MDA and MPO levels, restored GSH and SOD levels, and decreased (p<0.05) IL-6, IL-1β, and TNF-α levels, while increasing (p<0.05) IL-10 levels. Thus, these data suggest that carveol and hesperetin exhibit low toxicity with repeated doses, gastric healing activity, and duodenal anti-ulcer activity. These effects involve the participation of the antioxidant system and immunomodulation. Additionally, carveol has intestinal anti-inflammatory activity related to antioxidant and immunomodulatory activity, and this activity is possibly related to cytoprotective mechanisms.